DEVELOPMENT OF INTERNAL QUALITY ASSURANCE OPERATIONS BASED ON APARIHANIYADHAMMA IN THETSABAN 4 SCHOOL (BANLAMTRAI) UNDER SONGKHLA CITY MUNICIPALITY - Phutdam , Pricha; PhrakhruSumetPariyattikun; Srisuwan, Kasama (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to: 1) study the status of the internal quality assurance operation of Thetsaban School 4 (Ban Laem Sai), Songkhla Municipality, 2) study the development guidelines for the internal quality assurance operation of Thetsaban School 4 (Ban Laem Sai), Songkhla Municipality, and 3) present the development guidelines for the internal quality assurance operation of Thetsaban School 4 (Ban Laem Sai), Songkhla Municipality based on Aparihniyadhamma. This research is a qualitative research with 3 research steps: Step 1: Study the current state of internal quality assurance operations in educational institutions by conducting in-depth interviews with 15 relevant individuals. The data were analyzed using content analysis. Step 2: Explore approaches for improving internal quality assurance operations in educational institutions based on the principles of Aparihniyadhamma by conducting in-depth interviews with five experts. The data were analyzed using content analysis. Step 3: Present the proposed approaches for improving internal quality assurance operations in educational institutions based on the principles of Aparihniyadhamma through a focus group discussion with seven distinguished experts. The data were analyzed using content analysis. The research results found that: 1) The status of the operation of educational quality assurance within the educational institution was continuously carried out. The operations were as follows: (1) Setting educational standards, (2) Creating an educational development plan, (3) Implementing according to the plan, (4) Evaluating and inspecting quality, (5) Monitoring the results of the operation, (6) Preparing a self-evaluation report, (7) Developing the educational institution to be of quality, (8) Undergoing external quality assessment, (9) Applying recommendations from the analysis of the self-evaluation report (SAR) that had been carried out systematically but were not yet clear. 2) The guidelines for developing the operation of educational quality assurance within the educational institution according to the principle of Aparihniyadhamma had guidelines for applying the principle of non-corruption, consisting of (1) Regular joint meetings, (2) Working together in unity, (3) Adhering to and respecting good rules and regulations, (4) Respecting leaders and experts, (5) Complying with the rules and resolutions of the meeting, (6) Promoting equality in the organization, and (7) Praising good things. 3) The results of presenting the guidelines for developing the operation of educational quality assurance within the educational institution according to the principle of Aparihniyadhamma found that it was appropriate, feasible, and beneficial in the operation of educational quality assurance within the educational institution.